DIGITAL MANUFACTURING OF A METAL-CERAMIC IMPLANT-SUPPORTED PROSTHESIS - Bogdan Bulancea; Raluca Baciu; Alice Murariu; Roxana Vasluianu; Dana Budala; Gabriela Geletu (Romanian Society of Oral Rehabilitation, 2022)
Digital technology has been created to minimize therapy times for both clinicians and dental technicians, as well as to reduce the number of errors that occur with traditional methods. The purpose of this paper is to illustrate the technological processes of achieving metal-ceramic dentures in the context of full-arch rehabilitation on four implants, following the stages imposed by the digital systems in the dental technique laboratory. Digital laboratory techniques were used to aesthetically restore prosthetic restoration on implants. Among the devices used in the process of performing the works on the implant, we can mention the following: Scanner, 3D printers, laser milling and sintering devices, parallelograph, etc. Prosthodontic restorations on implants provide protection for the tissues at the level of the oral cavity. Maintaining the health of the oral cavity is a main objective of improving the quality of life. From indications point of view, depending on the clinical situation, we can say that metal-ceramic prosthesis is more indicated in extended edentations, due to resistance to fracture.